Implementasi Program Desa Bersinar (Bersih Narkoba) di Desa Pantai Cermin Kiri, Kabupaten Serdang Bedagai - Rafsanzani, Rafa; Atika, Tuti; Putri, Malida (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The Desa Bersinar (Drug Clean Village) program is a strategic initiative designed to prevent and eradicate drug abuse and illicit trafficking (P4GN) at the village level through the active involvement of both the village government and the community. This study aims to analyze the implementation of the Desa Bersinar program in Pantai Cermin Kiri Village, Serdang Bedagai Regency, an area recognized as drug-prone due to its coastal geographical conditions and its vulnerability to illicit distribution routes. The research adopts a descriptive qualitative approach, with data gathered through direct observation, in-depth interviews with the program coordinator, six implementing members, program beneficiaries, and two public informants. Additional data were obtained from documentation and relevant literature to provide a more comprehensive perspective. Data analysis was conducted through three stages: reduction, presentation, and conclusion drawing, ensuring systematic interpretation of findings. The results indicate that the Desa Bersinar program in Pantai Cermin Kiri Village has successfully implemented two of the three indicators outlined in David C. Korten’s theory of successful program implementation, specifically program elements and implementing organizational elements. These include clear structures of coordination, division of responsibilities, and collaboration among stakeholders. However, the third indicator—supportive environmental elements—has not been fully realized. Challenges include limited resources, lack of sustainable community participation, and insufficient external support from higher levels of government. Overall, the program demonstrates significant progress in combating drug-related issues, but its sustainability requires stronger environmental support, broader community empowerment, and multi-sectoral collaboration to ensure long-term effectiveness.